Supply of basic necessities to vulnerable populations during the COVID-19 pandemic: Empirical evidence from Shanghai, China - Wang, Qian; Dai, Ruiming; Zhang, Tiantian; Li, Jiaru; Sheng, Tao; Wu, Bin (Frontiers in Public Health, 2022)
Background In spite of initial widespread skepticism, city lockdown has been proved to be an effective short-term tool in containing and delaying the spread of a viral epidemic. The measures to ensure the supply of the basic necessities adequately and equitably, especially for those vulnerable ones has become a major challenge faced by all countries taking a city lockdown measure during the epidemic. Methods Data was collected through relevant government documents, work records, policy reports, media reports and the online-work information platform designed by the research group. Based on these references, the study analyzed the mainly technical difficulties and the countermeasures of the supply process, and summarized the key characteristics of basic necessities supply strategy for vulnerable groups in Shanghai. Results The supply strategy for vulnerable groups in Shanghai covers 16 districts, 232 streets and 6,028 neighborhood communities, which has already been in test running in April in some districts. The practical experience in Shanghai solved three key materials supply problems (lack of purchase channels, insufficient material reserves, insufficient transportation capacity) faced by government during the city lockdown, and showed three essential characteristics (overall coordination, community-centered intervention, technical support). Conclusions The findings in this study may provide some suggestions to other countries about how to better manage the preparation, dispatch and transportation of basic necessities in shortage for those vulnerable ones during the city lockdown.